English vocabulary acquisition among high proficiency ESL students from the perspective of involvement load hypothesis - Shu Qing, Seah; Khazriyati Salehuddin (Fakulti Sains Sosial dan Kemanusiaan, Universiti Kebangsaan Malaysia, 2022)
Vocabulary plays a crucial part in verbal exchange and is inevitable in second languageacquisition. A variety of hypotheses have been proposed to expound word acquisition; amongst the most significant and ef ective hypotheses is Laufer and Hulstijn’s Involvement Load Hypothesis. This study investigates the ef ectiveness of Involvement Load Hypothesis in English vocabulary acquisition among high proficiency ESL students through three dif erent task types (i.e., passage reading, gap-filling, and sentence writing). This study adopts the mixed-method research design. Thirty Bachelor of Arts with Honours (English Language Studies), Universiti Kebangsaan Malaysia (UKM) students were randomly assigned to these three groups to complete dif erent tasks. All participants were given an immediate post-test after the task completion, and another spontaneous delayed post-test one week later to measure their English word learning. Qualitative data were obtained through a semi-structured interview with nine students. Results show the following: participants in the sentence writing task group (the highest involvement index: four) showed better word retention than those in gap-filling task (involvement index: two), who, in turn, performed better than participants in the passage reading task (involvement index: zero). This suggests that active involvement in vocabulary tasks ensure the success of vocabulary learning.